2007
DOI: 10.1177/0044118x06296701
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Differences in Substance Use Among Black and White Adolescents

Abstract: Research reveals that Black youth are less likely to use alcohol than White youth. It has been argued that Blacks are more likely to abstain because they have less disposable income, are more religious, and have more family support and/or control than White youth. It has also been suggested that not only are these compositional characteristics different and likely to suppress use rates but also that the effects of these factors vary as well. However, there are no comprehensive empirical investigations of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our findings suggest that positive parenting factors that are protective for White boys and girls do not necessarily protect boys and girls from other racial and ethnic groups against alcohol use in the same way. Although there are many common risk and protective factors for adolescent alcohol use across racial, ethnic, and gender subgroups, risk and protective factors unique to each subgroup exist and should be addressed in prevention programs (Terling Watt & McCoy Rogers, 2007;Thai et al, 2010). Parent-based alcohol use prevention programs need to be culturally sensitive and account for gender differences.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Our findings suggest that positive parenting factors that are protective for White boys and girls do not necessarily protect boys and girls from other racial and ethnic groups against alcohol use in the same way. Although there are many common risk and protective factors for adolescent alcohol use across racial, ethnic, and gender subgroups, risk and protective factors unique to each subgroup exist and should be addressed in prevention programs (Terling Watt & McCoy Rogers, 2007;Thai et al, 2010). Parent-based alcohol use prevention programs need to be culturally sensitive and account for gender differences.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Few studies have examined the correlates of drinking behaviors in African American adolescents, however, and results are inconclusive (Vidourek & King, 2010). Differences in alcohol use patterns for youth of different ethnicities may be associated with differences in child conduct problems (Chartier, Hesselbrock, & Hesselbrock, 2009), depressive symptoms (Lombe,Yu, Nebbitt, & Earl, 2011; Maag & Irvin, 2005) and the effects of peer influence (Bossarte & Swahn, 2008; Watt & Rogers, 2007).…”
Section: Gender Race/ethnicity and Povertymentioning
confidence: 99%
“…These unexpected findings stand in contrast to previous research (Hurd et al, 2014; Mauer et al, 2021; Zimmerman et al, 2002) that found positive outcomes among youth who had an informal mentor in their life. Although it is possible that support from informal mentors is simply unrelated to ADV victimization or substance use involvement, we suspect it is more likely that ADV victimization and substance use involvement are determined by a confluence of factors that supersede the role of youths’ relationship with a mentor (Taquette & Monteiro, 2019; Watt & Rogers, 2007; Whitesell et al, 2013).…”
Section: Discussionmentioning
confidence: 98%